Tranexamic Acid Compared with Placebo for Reducing Total Blood Loss in Hip Replacement Surgery: A Randomized Clinical Trial. (April 2016) - Barrachina, Borja; Lopez-Picado, Amanda; Remon, Maria; Fondarella, Ana; Iriarte, Ibai; Bastida, Rebeca; Rodríguez-Gascón, Alicia; Achaerandio, Maria Aranzazu; Iturricastillo, Maria Carmen; Aizpuru, Felipe; Valero, Cesar Augusto; Tobalina, Ricardo; et al.
Abstract : BACKGROUND: Tranexamic acid (TXA) reduces bleeding in patients undergoing hip replacement surgery, but optimal doses and timing have yet to be established. Our primary objective in this study was to assess total blood loss 48 hours after surgery with different regimens. METHODS: This was a multicenter, parallel-group, randomized, placebo-controlled clinical trial that included all ASA physical status I to III patients undergoing unilateral total hip replacement surgery who met the inclusion criteria. Patients were randomly allocated to 1 of 3 groups: a single-dose group (15 mg/kg TXA before the start of surgery and saline 3 hours later after the start of surgery), a 2-dose group (10 m/kg TXA before and 10 mg/kg of TXA 3 hours after the start of surgery), and a control group (saline before and 3 hours after the start of surgery). Total blood loss was calculated using a formula considering hematocrit values and blood transfusions received. RESULTS: We included 108 patients in the study. Total blood loss volumes up to day 2 were 1377 ± 689, 1308 ± 641, and 2215 ± 1136 mL in the single-dose, 2-dose and control groups, respectively ( P < 0.001 between the placebo and the experimental groups). Blood transfusions were given to 22.9% of patients ( n = 8) in the single-dose group, 11.1% ( n = 4) in the 2-dose group, and 37.8% ( n = 14) in the control group ( P = 0.028). CONCLUSIONS: A single preoperative dose of TXA or 2 infusions of a lower dose, preoperatively and then after 3 hours after the start of surgery, resulted in lower blood loss during the first 2 days after surgery and less need for blood transfusion, with good levels of safety.